“Olhares” sobre o cotidiano da freguesia de nossa senhora da vitória (1848-1855) São Luís – MA 2018 - RODRIGUES , Tadeu Luis Maciel (2018)
The present work analyzes some aspects that included the daily slavery of the Parish of Our Lady of Victory of the eighteenth-century Maranhão capital, between the end of the 1940s and the beginning of the 1950s. In order to deal with such a challenge, we wished to trace the traces contained in First census book of the city of São Luis, 1855, articles of the Code of Posture of 1842 and records of the police force of the capital of Maranhão, in the Public Archive of the State of Maaranhão-APEM, concerning the years 1848 to 1854. In analyzing the conception, publication and organization of such documentary records, we intend to raise in the reader, how such documentary records can serve the historical interpretation, as "looks" of that parish and of the various variables concerning that historical period.